2017
DOI: 10.1177/0886260517729400
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Police Contact for Spousal Violence Survivors: The Role of Individual and Neighborhood Factors in Survivors’ Reporting Behaviors

Abstract: Rational choice theory proposes that spousal violence survivors engage in a cost-benefit analysis when determining whether to contact the police in the aftermath of violence. Feminist intersectional frameworks contend that the perceived costs and benefits of police intervention differ among survivors based on their intersecting social identities. Normative theory further posits that it is not solely individual factors but also social norms derived from one's neighborhood context that may be related to reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
12
0
5
Order By: Relevance
“…One is that we are only able to predict violent recidivism that is reported to police. Although more serious incidents of domestic abuse are more likely to be reported (Barrett et al 2017), we are unable to observe, and therefore to predict, violent domestic incidents that are not reported.…”
Section: Discussionmentioning
confidence: 56%
“…One is that we are only able to predict violent recidivism that is reported to police. Although more serious incidents of domestic abuse are more likely to be reported (Barrett et al 2017), we are unable to observe, and therefore to predict, violent domestic incidents that are not reported.…”
Section: Discussionmentioning
confidence: 56%
“…The Brisbane study reflects the outcomes of other studies in finding that it was usually the woman herself who called the police (Barrett, St Pierre and Vaillancourt 2011;Hamby 2014, 145) and women called for a variety of reasons (Barrett et al 2017;Barrett, St Pierre and Vaillancourt 2011;Leisenring 2012;Stewart, Mangan and Hannam 2013). Many of the Brisbane participants reported that police had been respectful towards them, listened to them, worked with them and followed up on their safety.…”
Section: Discussionmentioning
confidence: 75%
“…While women engaged a number of strategies in response to negative or inconsistent police responses, of most concern is that some women ultimately opted out of calling the police. This concern is reflected in other research that has shown that experiences with police have implications for the woman's decision about whether to call again (Barrett et al 2017;Goodman-Delahunty and Corbo Crehan 2015;Leisenring 2012;Li et al 2015). Research suggests that calling the police may help reduce future violence (Xie and Lynch 2017, 359).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations